Effects of Rearing Conditions and Sex on Cecal Microbiota in Ducks - Zhu, Chunhong; Xu, Wenjuan; Tao, Zhiyun; Song, Weitao; Liu, Hongxiang; Zhang, Shuangjie; Li, Huifang (Frontiers in Microbiology, 2020)
The intestinal microbiome influences the health of animals. However, little is known about the impact of indoor conditions and sex on intestinal microbiome diversity and composition in ducks. The present study aimed to investigate differences in the cecal microbiome between male and female ducks reared on the floor (PY group) or in cages (LY group). We also determined the relationships between cecal microbiota composition and slaughter traits, and the expression levels of mucosal and intestinal structural genes in ducks. There was a slight difference in slaughter traits among the groups, with cecum weight being significantly lighter in the LY compared with the PY group, especially in females (p<0.05). Analysis of the alpha diversity of the cecal microbiota between males and females in the LY and PY groups showed that LY males had significantly lower diversity and richness. Beta diversity analysis demonstrated differences in the microbiota composition in relation to rearing conditions, and a significant difference between the sexes in the PY groups. The dominant bacterial phyla in duck cecum were Bacteroidetes, Firmicutes, Proteobacteria, and Fusobacteria. The relative abundances of the most common bacteria revealed that the intestinal microbiota diversity and composition were affected by both feeding conditions and sex. Several bacterial genera were detected differentially among the groups, including Desulfovibrio, Anaerobiospirillum, and Erysipelatoclostridium. These genera and some other bacterial taxa were correlated with slaughter traits and expression levels of mucosal and cecal structural genes in ducks. In conclusion, the diversity and composition of the cecal microbiota in ducks were affected by both rearing conditions and sex. Rearing conditions, sex, and associated changes in the cecal microbiota are thus associated with gut barrier functions in ducks.